Tree Diversity Increases Forest Temperature Buffering via Enhancing Canopy Density and Structural Diversity - Florian Schnabel; Rémy Beugnon; Bo Yang; Ronny Richter; Nico Eisenhauer; Yuanyuan Huang; Xiaojuan Liu; Christian Wirth; Simone Cesarz; Andreas Fichtner; Maria D. Perles‐Garcia; Georg J. A. Hähn; et al. (Ecology Letters, 2025)
Global warming is increasing the frequency and intensity of climate extremes. Forests may buffer climate extremes by creating their own attenuated microclimate below their canopy, which maintains forest functioning and biodiversity. However, the effect of tree diversity on temperature buffering in forests is largely unexplored. Here, we show that tree species richness increases forest temperature buffering across temporal scales over six years in a large‐scale tree diversity experiment covering a species richness gradient of 1 to 24 tree species. We found that species richness strengthened the cooling of hot and the insulation against cold daily and monthly air temperatures and temperature extremes. This buffering effect of tree species richness was mediated by enhanced canopy density and structural diversity in species‐rich stands. Safeguarding and planting diverse forests may thus mitigate negative effects of global warming and climate extremes on below‐canopy ecosystem functions and communities.